2021
DOI: 10.1002/aic.17489
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven prescriptive maintenance toward fault‐tolerant multiparametric control

Abstract: Prescriptive maintenance can improve system effectiveness and system safety via integrated production and maintenance optimization. However due to system disruptions there is potential for abnormal operations and an undesirable increased occurrence of process safety incidents. This research provides a multiparametric‐based framework for safety‐aware, maintenance‐aware, and disruption‐aware process control. It leverages ensemble classification via machine learning classifiers for fault detection, mixed‐integer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…V refers to the current task. The execution time is represented by the ECT matrix of VP  , which is the time required to allocate each task to different nodes at the current moment [12]. In scheduling problems, the most common definitions are the earliest start time, earliest completion time, and maximum completion time.…”
Section: A Directed Acyclic Graph Task Scheduling In Heterogeneous En...mentioning
confidence: 99%
“…V refers to the current task. The execution time is represented by the ECT matrix of VP  , which is the time required to allocate each task to different nodes at the current moment [12]. In scheduling problems, the most common definitions are the earliest start time, earliest completion time, and maximum completion time.…”
Section: A Directed Acyclic Graph Task Scheduling In Heterogeneous En...mentioning
confidence: 99%
“…Math Prog. ML [27] 2022 GA [28] 2021 BH, VNS [29] 2021 GA, MC [30] 2021 GA [31] 2021 GA [32] 2021 GrA [33] 2021 GA [34] 2021 CEA [35] 2021 GrA [36] 2021 GA [37] 2021 BD [38] 2021 RHA [12] 2021 MP NN [39] 2021 RL [40] 2021 RL [41] 2020 GA [42] 2020 MVO [43] 2020 TS [44] 2020 NSGA-II [45] 2020 ANSGA-III [46] 2020 MA MIP [47] 2020 GA MIP [48] 2020 BOMP [49] 2020 BB [50] 2020 RL [51] 2020 RL [52] 2020 NN [53] 2019 GA [54] 2019 OTA [55] 2019 AC [56] 2019 NSGA-II [57] 2019 BIP [58] 2019 MILP [59] 2019 MINLP [60] 2019 RL [61] 2019 RL [62] 2019 RL [10] 2018 GA [63] 2018 SA, GA [64] 2018 SA [65] 2017 NSGA-II [66] 2017 MA [67] 2017 MILP [68] 2017 RL [69] 2016 NSGA-II [70] 2016 LPT MILP…”
Section: Yearmentioning
confidence: 99%
“…Elbasheer et al [10] suggested to incorporate RxM into production planning, and developed an intelligent decision support agent based on reinforcement learning. To cope with abnormal operations caused by system disruptions, Gordon and Pistikopoulos [11] proposed a multiparametric-based framework, which adopts ensemble classification for fault detection and mixed-integer nonlinear programming for safety-aware production and maintenance scheduling. However, for real production environments, production planning along with equipment status are often accompanied by a high degree of uncertainty and dynamics, which is a considerable challenge for maintenance program development.…”
Section: Introductionmentioning
confidence: 99%